KENDALA AMERIKA SERIKAT DALAM MEREGULASI PERUSAHAAN MEDIA SOSIAL META PLATFORMS - Ivan Borneva (Indonesian Journal of International Relations, 2024)
This research aims to analyze and understand what the obstacles for the United States are in regulating Meta Platforms (previously Facebook, inc.) which is the parent company of social media such as Facebook and Instagram. However, the various scandals that befell them further reduced US confidence regarding Meta's ability to carry out self-regulation. This research uses qualitative methods by collecting data through literature study and refers to two important elements of effective regulation proposed by Sheetal Radia. It was found that from the two senate sessions held, US senators, who on average became adults in an era without social media, still have a poor understanding of Meta's business model and how social media works. Also, the Federal Trade Commission, which is the main agency in dealing with data and privacy issues in the US, still has various limitations that make them less effective in reining Meta